Structural elucidation of essential oil of Ruta graveolens L. Ruda, antioxidant activity and cytotoxicity bio-assay - Castro L, Américo J. (2011)
Study objective was performing the structural elucidation of the essential oil of Ruta graveolens L. Ruda, determine its antioxidant activity and cytotoxicity testing. The complete plants were collected in Tarma, Region of Junin, and provided 1,80 kg of fresh leaves that were treated in a drag system with water vapor, obtaining performance of 0,3% v/p essential oil perfusion. The structural elucidation of chemical constituents of essential oil was performed by Gas Chromatography – Mass Spectrometry (GC-MS), stressing the identification of the following chemical components: 2-octanona 2-nonanona, nonanal, ciclohexen-5, 6-dietenil-1-methyl-, 2-decanona, nonyl ether, methyl 2-undecanona, ciclotetradecano, 2-dodecanona and 2-tridecanona. Evaluation of antioxidant activity in vitro of essential oil was made with the radical 2, 2-difenilpicrilhidrazil (DPPH) uptake method, demonstrating the radical DPPH antioxidant capacity as donor of electrons or hydrogen. The IC50 of essential oil was 16,13 mg/mL, high compared with acid ascorbic value, 2,4 μg/mL, and the capture of DPPH is relatively low. The cytotoxicity of essential oil on the embryonic development of Tetrapygus niger, black sea urchin, showed at concentrations of 50 and 75 μL altered eggs, lysis, delayed development and embryos that not made division. To concentration of 100 μL stopped development.